Gaya Kepemimpinan Transformasional Menjadi Faktor Dominan dalam Memengaruhi Kepuasan Kerja Pegawai PLN XYZ - Ardyansyah, Wahyu Catur; Nuryanto, Imam; Astuti, Sih Darmi; Ulfa, Adilla Kustya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The primary objective of this research is to examine how deeply Transformational Leadership Style, Reward Provision, and Work Discipline shape the level of Job Satisfaction. To achieve this goal, a causal-comparative quantitative framework was employed as the methodological foundation of the study, with the aim of knowing the relationship between the causes and effects of each variable that is the object of research. Questionnaires were distributed directly to all PLN XYZ employees as the main instrument for gathering primary data, yielding 93 respondents whose responses were deemed valid and eligible for further analytical processing. The sample determination in this research was carried out by applying the census method, which means that all members of the population were fully involved as respondents in the research. The collected dataset was then examined through multiple linear regression analysis utilizing the SPSS software, which involved a comprehensive set of statistical procedures including multiple linear regression, t-test, f-test, and coefficient of determination. Three key conclusions emerged from the findings of this research transformational leadership style holds a positive and significant role in shaping the job satisfaction experienced by employees of PLN XYZ, the provision of rewards similarly carries a positive and significant role in elevating the job satisfaction of PLN XYZ employees, work discipline consistently demonstrates a positive and significant role in strengthening the job satisfaction felt by employees at PLN XYZ.